2002
DOI: 10.1089/109065702760093843
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of MECP2 Mutations in Rett Syndrome

Abstract: Mutations in the MECP2 (Methyl-CpG-binding protein) gene recently have been reported to cause Rett syndrome (RTT), an X-linked progressive encephalopathy. We have collected the results of MECP2 analysis conducted in four laboratories in France. A total of 301 RTT alleles have been analyzed, demonstrating a total of 69 different mutations so far observed and accounting for 64% of MECP2 genes in RTT patients living in France. R168X (11.5%) is the most common of MECP2 mutations, followed by R255X (10.9%), R270X (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…Amino acids Arg-106 and Phe-155 have side chains that both contribute to the hydrophobic core of the MBD domain (19) and are mutated to tryptophan and serine, respectively, in specific Rett syndrome cases. Further occurrences of the R106W mutation have since been identified (13,16,18), and R106Q and F155I mutations have also recently been found in Rett syndrome patients (14,18). The R106W protein was found to bind methylated DNA very poorly, whereas the F155S mutant, although forming a complex at fairly low protein concentrations, did not shift the probe to completion (Fig.…”
Section: Missense Mutations Found In Rett Syndromementioning
confidence: 85%
See 2 more Smart Citations
“…Amino acids Arg-106 and Phe-155 have side chains that both contribute to the hydrophobic core of the MBD domain (19) and are mutated to tryptophan and serine, respectively, in specific Rett syndrome cases. Further occurrences of the R106W mutation have since been identified (13,16,18), and R106Q and F155I mutations have also recently been found in Rett syndrome patients (14,18). The R106W protein was found to bind methylated DNA very poorly, whereas the F155S mutant, although forming a complex at fairly low protein concentrations, did not shift the probe to completion (Fig.…”
Section: Missense Mutations Found In Rett Syndromementioning
confidence: 85%
“…The mutation S134A was also seen to cause a moderate reduction in binding affinity. Ser-134 was found to be mutated to cysteine in cases of Rett syndrome (14,16), and the reduction in binding affinity caused by mutating this residue may thus contribute to the pathology.…”
Section: Emsa Analysis Of Dna Binding By Mecp2 Mbd Mutants-mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have found an association between skewed X inactivation and a milder phenotype, 17,26,28,31 whereas one study also found an association between skewed X inactivation and a more severe phenotype. 28 Our results support the reported association between a milder phenotype and skewed X inactivation, as we found a higher mean degree of skewing in mild cases than in moderate or severe cases.…”
Section: Discussionmentioning
confidence: 97%
“…Stabilization generally occurs and most patients survive into adulthood (Rett, 1966;Hagberg et al, 1983;Hagberg, 1985). In the past year, several groups have reported similar ®ndings, expanding the number of MeCP2 mutations reported to in excess of 90 mutations in more than 400 individuals Buyse et al, 2000;Bienvenu et al, 2000;Cheadle et al, 2000;Hampson et al, 2000;Huppke et al, 2000;Kim and Cook, 2000;Obata et al, 2000;Wan et al, 1999;Xiang et al, 2000). Most groups report that more than 80% of classic Rett cases examined have mutations in the X-linked MeCP2 gene.…”
Section: Rett Syndrome and Mecp2mentioning
confidence: 96%